2021
DOI: 10.3389/fphar.2021.659258
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Cohort Study of Intraoperative Administration of Sustained-Release 5-Fluorouracil Implants in Advanced Gastric Cancer Patients

Abstract: Background: 5-fluorouracil (5-FU) is basically used in the field of postoperative chemotherapy of gastric cancer (GC), the goal of this study was to evaluate improvement of long-term survival rate among GC patients after the 5-FU implants treatment.Methods: The study included 145 patients with gastric cancer who received postoperative chemotherapy with 5-FU implants and had complete follow-up information. According to the sex, age and clinical stage of 5-FU implants group, 74 patients were matched as the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…The use of sustained-release 5-FU implants has shown survival benefits in different types of digestive system tumors such as colon cancer and primary hepatic cellular cancer[ 29 , 30 ]. Furthermore, a few studies on the treatment of gastric cancer, which showed similar results, were also reported by Chinese researchers[ 21 , 22 ]. However, P values of survival benefits obtained in previous studies on gastric cancer were lower, but close to 0.05.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The use of sustained-release 5-FU implants has shown survival benefits in different types of digestive system tumors such as colon cancer and primary hepatic cellular cancer[ 29 , 30 ]. Furthermore, a few studies on the treatment of gastric cancer, which showed similar results, were also reported by Chinese researchers[ 21 , 22 ]. However, P values of survival benefits obtained in previous studies on gastric cancer were lower, but close to 0.05.…”
Section: Discussionsupporting
confidence: 65%
“…The use of sustained-release 5-FU implants intraoperatively is a relatively newly developed method and has been used widely in almost all types of digestive tract cancer in China[ 20 ]. When this drug was placed intraoperatively into the tumor bed, it was released continuously, and it maintained a locally high drug concentration for approximately 1 mo[ 21 ]. The potential remnant tumor tends to grow quickly in the first year after resection owing to the decreased immunity and absence of adjuvant chemotherapy[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation